A study of electrocardiographic changes in congenital deaf school children - Chinagudi, Surekharani (Springer-Verlag, 2010)
BACKGROUND: There is evidence of cardiac abnormalities in congenital deaf school children, together called as Jervel Lange Nielsen syndrome or Long QT syndrome. AIM: The main aim was to study the electrocardiographic changes in congenital deaf children. MATERIALS AND METHODS: Fifty congenital deaf children aged 6–18 years were selected. ECG was taken in lead II, at rest and after exercise, as some are known to exhibit the abnormality after exercise. The child was made to run on the Tread mill till exhaustion. Corrected QT interval (QTc) was Calculated by Bazett’s formula QTc = QT/ √R-R. ECG was also analyzed for other abnormalities like Twave changes, ST depression, rhythm abnormalities etc. RESULTS: Out of 50, 2 children showed resting QTc of 0.45 sec which is diagnostically high. Mean value of QTc in deaf children(Cases) before exercise was 0.4111 ± 0.0271 sec and in controls 0.379 ± 0.020 sec. Mean value of QTc after exercise in deaf(cases) was 0.403 ± 0.028 sec and in controls 0.376 ± 0.021 sec. Eight deaf children showed ST depression and 2 biphasic T and 2 notched T waves. Thirty-three deaf children’s parents had consanguineous marriage. CONCLUSION: The results were explained on the basis of ion channellopathy in heart and inner ear which predisposes to sensorineural hearing loss and cardiac abnormality.